Investıgatıon Of Respıratory Parameters, Hand-Eye Coordınatıons And Body Mass Indexes Of Superior İntelligence Students Between 8 And 9 Years - Faruk Akçınar; Mehmet Güllü; Serpil Akçınar; Cengiz Arslan (Türk Spor ve Egzersiz Dergisi)
The aim of this study was to investigate respiratory parameters, hand-eye coordination and body mass indexes of gifted students aged 8-9 years. The population of the research consists of 124 students from 23,228 students in the second year in Malatya. The research group consists of 73 students (37 girls and 36 boys). To determine students' intelligence levels as data collection tools Wechsler Intelligence Scale for Children (Savaşır and Şahin, 1995) was applied, Mir Spirolab III brand spirometer is used for measurement of the functions, dart was performed for hand-eye coordination and weight and height measurements were taken for Body Mass Index (BMI). One - way ANOVA was used for comparisons. Significance level was tested with α = 0.05. The findings of the study showed that children with normal intelligence (n = 4) Wisc-r had a total of 105.75 ± 2.36; children with bright intelligence (n = 10) 114.30 ± 2.40; children with superior intelligence (n = 26) 124.30 ± 2.71; children with very high intelligence (n = 22) 134.18 ± 2.48; genius group (n = 11) children were found to score 145.73 ± 3.95. There was no statistically significant difference (p gt; 0.05) between FVC, FEV1, PEF, Dart mean and BMI according to intelligence groups of children. As a result, there was no significant difference between respiratory parameters, hand-eye coordination and BMI according to intelligence levels of 8-9 years old children. Therefore, it can be said that gifted children do not have any physical difference compared to the children in the other intelligence group.